Binomial Models in Finance - Hoek, John van der.; Elliott, Robert J.; SpringerLink (Online service) (New York, NY : Springer New York, 2006)
This book deals with many topics in modern financial mathematics in a way that does not use advanced mathematical tools and shows how these models can be numerically implemented in a practical way. The book is aimed at undergraduate students, MBA students, and executives who wish to understand and apply financial models in the spreadsheet computing environment. The basic building block is the one-step binomial model where a known price today can take one of two possible values at the next time. In this simple situation, risk neutral pricing can be defined and the model can be applied to price forward contracts, exchange rate contracts, and interest rate derivatives. The simple one-period framework can then be extended to multi-period models. The authors show how binomial tree models can be constructed for several applications to bring about valuations consistent with market prices. The book closes with a novel discussion of real options. John van der Hoek is Senior Lecturer in Applied Mathematics at the University of Adelaide. He has developed courses in finance for a number of years at various levels and is a regular plenary speaker at major conferences on Quantitative Finance. Robert J. Elliott is RBC Financial Group Professor of Finance at the Haskayne School of Business at the University of Calgary. He is the author of over 300 research papers and several books, including Mathematics of Financial Markets, Second Edition (with P. Ekkehard Kopp), Stochastic Calculus and Applications, Hidden Markov Models (with Lahkdar Aggoun and John Moore) and Measure Theory and Filtering: Theory and Applications (with Lakhdar Aggoun). He is an Associate Editor of Mathematical Finance, Stochastics and Stochastics Reports, Stochastic Analysis and Applications, and the Canadian Applied Mathematics Quarterly.
The Binomial Model for Stock Options -- The Binomial Model for Other Contracts -- Multiperiod Binomial Models -- Hedging -- Forward and Futures Contracts -- American and Exotic Option Pricing -- Path-Dependent Options -- The Greeks -- Dividends -- Implied Volatility Trees -- Implied Binomial Trees -- Interest Rate Models -- Real Options -- The Binomial Distribution -- An Application of Linear Programming -- Volatility Estimation -- Existence of a Solution -- Some Generalizations -- Yield Curves and Splines.
Keywords: Statistics; Economics, Mathematical; Economic theory; Statistics; Statistics for Business/Economics/Mathematical Finance/Insurance.; Economic Theory/Quantitative Economics/Mathematical Methods; Quantitative Finance; Electronic books